2006
DOI: 10.1017/s1047951106000977
|View full text |Cite
|
Sign up to set email alerts
|

Correlations with operative anatomy of real time three-dimensional echocardiographic imaging of congenital aortic valvar stenosis

Abstract: We recommend trans-thoracic real time three-dimensional echocardiography for the assessment of the congenitally malformed aortic valve, particularly to identify sites of fusion between leaflets and to measure the orificial diameter. The definition of nodularity, and the prognosis of nodules based on the mode of intervention, will need a comparative study of patients submitted to balloon dilation as well as those undergoing surgical valvotomy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
12
0

Year Published

2009
2009
2021
2021

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(12 citation statements)
references
References 6 publications
0
12
0
Order By: Relevance
“…The relation of the anterior leaflet of the mitral valve to the LVOT can be depicted with high precision using RT 3D TOE aiding in the accurate placement of these stent based prosthesis [CoreValve] for the treatment of aortic stenosis. Sadagopan et al showed that 3DE provided accurate measurements of aortic valve annulus and number of valve leaflets, in identifying sites of fusion of the leaflets as well as nodules and excrescences that characterized dysplastic valves [26]. …”
Section: Three Dimensional Echocardiographymentioning
confidence: 99%
“…The relation of the anterior leaflet of the mitral valve to the LVOT can be depicted with high precision using RT 3D TOE aiding in the accurate placement of these stent based prosthesis [CoreValve] for the treatment of aortic stenosis. Sadagopan et al showed that 3DE provided accurate measurements of aortic valve annulus and number of valve leaflets, in identifying sites of fusion of the leaflets as well as nodules and excrescences that characterized dysplastic valves [26]. …”
Section: Three Dimensional Echocardiographymentioning
confidence: 99%
“…Other clinical applications include visualisation of sub-aortic pathology and complex left ventricular outflow tract obstructions,9 double chambered ventricles, and variation in septal morphology (figure 4) and its defects 13 . w9 w10 3DE is also used in understanding the morphological details of the aortic valve and accurate measurement of the valve area, aiding in appropriate catheter interventions14 (figure 5). Mitral valve planimetry and quantification of regurgitation using advanced 3D software is now possible as it “provides complementary information as to the mechanisms and sites of AV valve failure in congenital heart disease” 15 .…”
Section: Clinical Application Of Rt3de In Specific Congenital Heart Dmentioning
confidence: 99%
“…Though some progress has been made in 3DE,14 19 age, sex and body weight matched standardised normal values for cardiac chambers and vessels is an important requirement. Similarly, quantification of myocardial deformation in both biventricular and univentricular circulation in pre- and postoperative states is essential to define and understand the progression of pathology.…”
Section: Future Directionsmentioning
confidence: 99%
“…RT3DE was also used to define congenitally severe aortic stenosis, and the results from RT3DE were compared with the valve morphology observed during surgery. The sites of fusion of the leaflets were correctly identified by RT3DE in all cases [65].…”
mentioning
confidence: 92%